Microstructure, Mechanical Properties and Fire Resistance of High Strength Mg-Gd-Y-Zr Alloys - Qian, Yafeng; Zhao, Yanhui; Dong, Xiaorui; Yu, Wei; Feng, Jianhang; Yu, Hui (Metals (Basel ), 2022)
With the lightest green structural material for 21st century, a significant weight reduction effect was expected to solve the lightweight problem in aerospace and other fields. However, the material’s poor mechanical properties and flammability limited its widely application in such fields. In this paper, the GWK series alloys (Mg-5.3Gd-4.11Y-0.13Zr, Mg-5.5Gd-4.22Y-0.19Zr, and Mg-5.46Gd-4.02Y-0.20Zr, in wt.%) were designed, and we explored the effect of alloy composition and process on the microstructure and properties of GWK series alloys subject to casting, homogenization, extrusion, ageing and ignition. The result show that Mg-5.3Gd-4.11Y-0.13Zr alloy after T4 treatment at 500 °C/6 h obtains an excellent solid solution effect. In addition, the aged alloy shows a good balance of mechanical properties, a tensile strength of 405 MPa, yield strength of 275 MPa, as well as elongation of 8.12%, and excellent non-flammability.